Diode-Pumped 50 Hz–10 J Nano-Second Nd:YAG Laser - Jiang, Xinying; Xiao, Kaibo; Yan, Xiongwei; Wang, Zhenguo; Jiang, Xuejun; Xue, Qiao; Wu, Wenlong; Chen, Ji; Zhang, Chuanchao; Zheng, Jiangang; Peng, Zhitao; Zheng, Kuixing; et al. (Frontiers in Physics, 2022)
In this letter, we report a diode-pumped nano-second laser with the output energy 10 J, the repetition rate 50 Hz, and the average power 500 W. The main amplifier was made up of eight amplify modules. Each amplify module was pumped by an 808 nm laser diode and cooled by water from the back end of the Nd:YAG slab. To our knowledge, this represents the highest pulse repetition rate for the 10 J class nano-second single-aperture Nd:YAG laser. The beam quality was controlled by means of mechanical design and adjustment and compensation by a home-made deforming mirror. The beam quality was controlled well with the beam quality of the laser 2.61DL.